Perceptions about children and adolescents’ mental health crisis intervention: a qualitative systematic review - Telles, Nathalia Nakano; dos Santos Cruz, Nathalia; Cardoso, Marilia Mastrocolla de Almeida [UNESP]; de Oliveira Luz, Priscilla; Fernandes, Heloísa Garcia Claro; de Oliveira, Márcia Aparecida Ferreira (FapUNIFESP (SciELO), 2024)
This review aimed to identify and synthesize the perceptions of mental healthcare professionals, family members, and users about mental health crisis interventions for children and adolescents at hospitals and community mental health services. A qualitative systematic review was conducted following the Joanna Briggs Institution guidelines. The search was performed in 15 databases, with no temporal delimitation, and included studies in Portuguese, English, and Spanish. All works were assessed regarding methodological quality, credibility, and dependability according to the ConQual score and the recommendations were assessed following the Joanna Briggs Institution guidelines. In total, two independent reviewers screened and assessed the studies, extracted their data, developed categories, and conducted the thematic synthesis. A total of 13 studies met the inclusion and exclusion criteria. From these, five syntheses were developed: importance of relationships; importance of procedures during treatment; positive emotional responses to treatment; negative emotional responses to treatment; and issues with health professionals and health services. All five syntheses presented high dependability; two syntheses presented high credibility; and three presented moderate credibility. Mental healthcare professionals, family members and users had convergent perceptions about crisis intervention provided at healthcare services. Understanding their perceptions to improve care and the user experience in this vulnerable situation is crucial.
Percepciones sobre la intervención en crisis de salud mental en niños y adolescentes: una revisión sistemática cualitativa
Percepções sobre a intervenção em crises de saúde mental de crianças e adolescentes: uma revisão sistemática qualitativa
Keywords: Adolescent; Child; Crisis Intervention; Mental Health; Perception